Commemorative events in the Omsk region (1937) on the occasion of 100th anniversary of death of A. S. Pushkin - K. A. Tishkina (Омский научный вестник: Серия "Общество. История. Современность")
One of the significant events of 1937 in the USSR was the celebration of the 100th anniversary of the death of A. S. Pushkin, which contributed to attracting the attention of Soviet citizens to the life and work of the poet. The purpose of this work is to examine the process of organizing and holding Pushkin Days in settlements of the Omsk region. The choice of the region is connected with the coverage of a large territory, which was inhabited by different populations. The research is based on a number of unpublished documents from the funds of the Historical Archive of the Omsk region, as well as materials of the periodical press of the Omsk region for 1936–1937. In conclusion, it is noted that the celebration of the anniversary of the poet’s death significantly influenced the development of cultural life in the USSR, helped to attract the population to the problem of illiteracy, attracted the indigenous population of Siberia to participate in the event.